Safeguards Assessments : 2007 Update. (Policy Papers; Policy Paper ;, 2007)
This paper provides Executive Directors with an update of safeguards assessment activities from July 1, 2006 through June 30, 2007. This is the second annual update report of safeguards activities since the last review of the safeguards policy in April 2005. The next review of the policy by the Executive Board is scheduled for 2008.